PENGARUH BRAND EQUITY DAN ONLINE REVIEWS TERHADAP MINAT BELI ONLINE GENERASI MILLENIAL DI KOTA PADANG - Rihan Hafizni; Evita Sandra (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The growth of the internet is affecting marketing systems that are changing from conventional to digital systems. It's important for business owners to know what factors are causing interested consumers to buy. After conducting research on 100 respondents on brand equity factors (brand awareness, perceived quality, brand association, brand loyalty) and online reviewss on online purchase interest in millennials in Padang city. The results showed that brand awarness being in important factor but brand loyalty were negative and significant that influenced online purchase intention millennials in Padang City. This research made the